2014
DOI: 10.1097/icl.0000000000000002
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Tear Osmolarity Using the TearLab Osmolarity System in Normal Adults in Saudi Arabia

Abstract: We found that the average osmolarity for subjects living in Saudi Arabia was 299.06±7.65 mOsm/L, which falls within the reference range and is in agreement with published results (298.0-301.9±7.2-16.0 mOsm/L). Osmolarity was positively correlated with McMonnies questionnaire and negatively correlated with TBUT values. The TearLab osmolarity system test showed good precision in repeated measurements. This is the first report of use of the TearLab osmolarity system to assess tear film in normal Saudi adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 48 publications
(44 citation statements)
references
References 45 publications
3
35
1
Order By: Relevance
“…represented normal values for healthy eyes. [34][35][36][37] There is no previous report on osmolarity values in CM, and these were statistically similar to those of humans in our study, emphasizing the similarity of the two species' tear films.…”
Section: Descriptions Of Tear Osmolarity Have Previously Been Reportedsupporting
confidence: 75%
“…represented normal values for healthy eyes. [34][35][36][37] There is no previous report on osmolarity values in CM, and these were statistically similar to those of humans in our study, emphasizing the similarity of the two species' tear films.…”
Section: Descriptions Of Tear Osmolarity Have Previously Been Reportedsupporting
confidence: 75%
“…This study, conducted in healthy subjects, showed inter‐session reproducibility of the Fiske 110 osmometer with two different tear samples volume (2 or 4 μl). Osmolarity values obtained here (Table ) were lower than those widely assumed by the literature in healthy subjects as ‘common’, but similar to those previously reported by Garcia et al when using a similar protocol and device (a 1:9 dilution measured by the Fiske 210). Osmolarity values obtained were also in concordance with those previously reported by the present authors with the same dilutions and protocols in two groups of 60 healthy patients (Fiske 110 [4 μl] mean ± SD = 286.53 ± 16.54 mOsm/kg; Fiske 110 [2 μl] mean ± SD = 268.80 ± 30.53 mOsm/kg) …”
Section: Discussionsupporting
confidence: 89%
“…Hyperosmolarity may also be negatively associated with BUT and positively with the DE diagnostic questionnaire by McMonnies in mild‐to‐moderate patients with DED; other studies, however, have only found weak, but significant association between high hyperosmolarity and lower LL thickness, changes in symptoms and dry spot formation (fluorescein staining) . One study was unable to find associations between hyperosmolarity and reported DE symptoms and frequency among mild‐to‐moderate patients with DED (mean age = 28 years); however, the study, apart from relatively young subjects, is hampered by a number of factors as discussed by the authors.…”
Section: Resultsmentioning
confidence: 82%